Peran Konsultan Teknologi Informasi dalam Mendukung Implementasi Good Corporate Governance - Lutfy, Arjuna (Universitas Multi Data Palembang, 2025)
The adoption of information technology that is being intensively carried out by companies in this decade results in companies having to do good management in order to support business needs. Information technology governance is an important aspect in companies, especially those that have adopted or invested in information technology. In the digital transformation carried out by the company, it is important for the company to pay attention so that IT governance is in line and does not conflict with the principles of Good Corporate Governance (GCG). One of the efforts made by companies to plan, implement, and evaluate IT governance is to get help from professionals called information technology consultants. However, the efforts made by information technology consultants must be ensured in accordance with the principles of Good Corporate Governance (GCG). By conducting observations, interviews and direct involvement of researchers in IT consulting projects, data was collected from the type of work done by one of the information technology consulting companies in Indonesia. Mapping was done to illustrate the suitability of the consultant's role with the five pillars of Good Corporate Governance principles. The results show that the role of IT consultants is relevant and in line with the five pillars of GCG